2009
DOI: 10.1038/hr.2009.79
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia is associated with decreased serum α2-HS glycoprotein (fetuin-A) concentration

Abstract: The purpose of this study was to determine serum a 2 -HS glycoprotein (AHSG) concentration and its diagnostic accuracy in preeclampsia. In this case-control study, the serum C-reactive protein (CRP) and AHSG levels were measured in 93 preeclamptic patients and in 127 healthy pregnant women by immunoturbidimetry and radial immunodiffusion. The serum CRP levels were significantly higher, whereas the serum AHSG concentrations were significantly lower in the preeclamptic group than in the control group (median (25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 53 publications
3
16
0
1
Order By: Relevance
“…These results indicated that BMI was significantly higher in the PE group than that in the control group, as noted previously (15). Previous studies found that overweight and obese women have elevated risks of PE, cesarean delivery, and childhood obesity compared with normal-weight women (16).…”
Section: O R I G I N a L A R T I C L Esupporting
confidence: 75%
See 1 more Smart Citation
“…These results indicated that BMI was significantly higher in the PE group than that in the control group, as noted previously (15). Previous studies found that overweight and obese women have elevated risks of PE, cesarean delivery, and childhood obesity compared with normal-weight women (16).…”
Section: O R I G I N a L A R T I C L Esupporting
confidence: 75%
“…This decrease may be due to the fact that all PE women had proteinuria, and fetuin-A was excreted in urine with other small-molecular-weight proteins. Low fetuin-A was also reported in other studies (15,29). Furthermore, fetuin-A has been implicated in the pathophysiology of PE (7,8).…”
Section: Sfetuin-a In Patients and Controlsmentioning
confidence: 51%
“…Thirty‐two studies in total reported on C‐reactive protein levels,21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52 of which 17 were applicable for meta‐analysis 21, 22, 23, 29, 30, 31, 32, 33, 34, 37, 38, 39, 41, 42, 47, 49, 50. A significantly higher C‐reactive protein was found in women with pre‐eclampsia than in non‐hypertensive controls ( Figure 2), and this correlation was stronger in severe than in mild pre‐eclampsia ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…2 The development of pre-eclampsia is influenced by both genetic and environmental risk factors, suggesting its multifactorial inheritance. [3][4][5][6][7][8][9][10][11][12] Soluble fms-like tyrosine kinase-1 (sFlt-1), the naturally occurring soluble form of vascular endothelial growth factor receptor 1 (VEGFR1), is produced by alternative splicing of the Flt-1 transcript, resulting in a deletion of the intracellular and transmembrane domains of Flt-1. sFlt-1 binds VEGF and placental growth factor (PlGF) with high affinity, acting as a soluble trap of these angiogenic factors.…”
Section: Introductionmentioning
confidence: 99%